Financial Management Training for Entrepreneurs: Enhancing Decision Making and Financial Independence at Erawadee Company, Thailand - Ingga Maulana; Andry Sugeng; N Rusnaeni (Journal of Innovation and Sustainable Empowerment, 2026)
This Community Service (PKM) activity aims to improve the financial management skills of business actors at Erawadee Company, Thailand, so they can make more appropriate business decisions and support the achievement of financial independence. In the context of increasingly fierce business competition, especially in the herbal business sector, effective financial management is a crucial factor in maintaining business sustainability. The PKM implementation method uses a participatory and applied approach that includes socialization, training in simple financial recording, cost management, budgeting, and individual mentoring and consultation. The activity was carried out at Erawadee, Pattaya, Chon Buri, Thailand, on August 4–8, 2025, involving business owners, employees, and MSME actors within the Erawadee Company environment. The activity was evaluated through pre-test and post-test measurements of participants' understanding of aspects of financial recording, cost control, budgeting, and financial-based decision-making. The evaluation results showed an increase in the average score in all aspects measured after the implementation of the activity. Participants were also able to apply simple financial management practices to their daily business activities, resulting in increased efficiency, transparency, and the quality of business decision-making. Thus, this PKM activity contributes to improving financial literacy and supporting efforts to strengthen the financial independence of business owners in the Erawadee region.